Analisis Penyusutan Aktiva Tetap Dengan Metode Garis Lurus Terhadap Laba Pada PT Bakti Pertiwi Nusantara - Ramadhan, Phijar; Santoso, Bambang; Sianturi, Murdan (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2024)
In general, the purpose of establishing a company is to obtain a very optimal profit on the investment that has been invested and to be able to maintain business continuity in the long term.Accounting is a process of recording, classifying and summarizing financial transactions that are arranged systematically and chronologically and are presented in the form of financial reports that are useful for related parties for decision making. Assets are economic resources acquired and controlled by a company as a result of past transactions, one of which is fixed assets used by the company in the company's operational activities in producing products. The depreciation method is a method used to allocate the cost of fixed assets to an expense. The main variables that must be considered in this allocation include: the cost of fixed assets. Residual value (salvage value) and estimated useful life (estimated useful period)The research method uses descriptive quantitative methods, all the data were examined from companies as a result of interviews and documentation, so researchers analyzed research from financial reports such as balance sheets and income statements.The results and discussion contain the results of the analysis of the researchers who have been analyzed, calculating a company's assets using the straight-line method which affects a company's profit and seeing how far the company uses the depreciation method whether it is in accordance with SAK provisions or notAs for the conclusions and suggestions, the author concludes that the results of this study can be concluded that the company uses the straight-line depreciation method, that the company from the percentage of ages with groupings is not in accordance with SAK, therefore it must be checked against the depreciation method applied by the company so that it can comply with Financial Accounting Standards The method of depreciation of fixed assets has an effect on company profits, which proves that for depreciation determined by the company with that determined by the SAK, it has a far comparison in profit and loss at the corporate rate, resulting in a net profit of Rp. 15,061,177,215 and for SAK rates of Rp. 15,314,152,304, if the company wants to make a profit, the company in calculating depreciation must apply a rate that is in accordance with SAK so that errors do not occur again